The controversy surrounding the conquest and the Islamisation of Bosnia. Contribution to the critique of the so-called “historical politics” - Wróbel, Piotr (Balcanica Posnaniensia. Acta et studia, 2012)
The statement is a reference to the article <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">Islamization of Bosnia in the XV-XVIth century, published last year in “Balcanica Posnaniensia. Acta et studia” vol. XVIII. A critical analysis of sources and a confrontation of studies made by different historians shows that the process of conquest and Islamization of Bosnia was similar (but not identical, of course!) as in the case of the other Balkan countries. The reasons for the extraordinary religious situation in contemporary Bosnia, therefore, should be sought in the events of later periods. Overview of the opinions on issues of Islamization and the Turkish conquest suggests that there is an amazing difference among historians. In the author’s opinion largely it results from causes not substantive and is rather politically motivated. Such events of the medieval past as: the history of the Bosnian Manicheans, Ottoman conquest of Bosnia or the process of Islamization become the building blocks of modern national identity of Bosnian Muslims, ie. Bošnjaks. These problems have become a part of the so-called. “Historical Politics” that resulted in very bad consequences. Author notes that the compromises, the selection of facts under a given hypothesis or to formulating opinions in the “name of higher reason” immediately brings fatal consequences and is counterproductive. The so-called “Historical Politics”, even in its mildest version, entails an instrumental treatment of the history. Such practices should always be condemned by scholars and teachers.